What to feed your baby : a pediatrician's guide to the eleven essential foods to guarantee veggie-loving, no-fuss, healthy-eating kids - Altmann, Tanya Remer (HarperOne, 2016)
"A practicing pediatrician, bestselling author, and spokesperson for the American Academy of Pediatrics offers a simple, fool-proof, no fuss plan for raising kids who love eating nutritious food. As a pediatrician and mother of three boys, Dr. Tanya Altmann knows that good nutrition is essential for healthy kids. But parents today are bombarded with confusing, and sometimes harmful, information. Nutritional guidelines are constantly changing, and parents don't know who to trust for medically sound, proven advice that works. In How to Feed Your Baby, Dr. Tanya cuts through the noise with a simple program that follows the safest, best practices for feeding babies and young children. She begins with the eleven foundation foods critical to brain development and growth--eggs, prunes, avocado, fish, yogurt/cheese/ milk, nuts, chicken/beans, fruit, green veggies, whole grains, and water--that should be the basis of every child's diet in the three phases of their early life: infancy, toddler, and preschooler. She also offers guidance and information for introducing them into a child's daily diet, and delicious, dietician-developed recipes that will help train young taste buds to enjoy and desire real, whole, non-processed foods. With How to Feed Your Baby parents will save time, money, and stress--and say goodbye to picky eating!"--